Le cosmopolitisme et l’étrangéisation : Anna Nakwaska (1781-1851) et les géographies de la littérature polonaise d’expression francophone - Bajer, Michał (Studia Romanica Posnaniensia, 2023)
The studies on Polish francophone literature put an emphasis on a selected group of authors (Potocki, Mickiewicz, Krasiński) and on some literary genres (diary and travelogue). The aim of this paper is to study the work of a lesser-known feminine writer, Anna Nakwaska, member of cosmopolitan literary milieu and author of several short stories and novels, written in French. Applying selected concepts of spatial literary studies, the first part of the article proposes to perceive the publishing strategies of Nakwaska as a tool for introducing Polish feminine literature in a broader European context. In the second place, the study of some Nakwaska’s short stories show her interest for a literary presentation of several geographical problems, including demography (put in the context of antisemitism) and regional ecology. The use of Polish toponymy brings a foreignization of the francophone fiction.